2008
DOI: 10.1002/mrm.21615
|View full text |Cite
|
Sign up to set email alerts
|

Concomitant field terms for asymmetric gradient coils: Consequences for diffusion, flow, and echo‐planar imaging

Abstract: As a consequence of the Maxwell equations, linear field gradients are accompanied by additional spatially dependent field components. A description of the Maxwell field terms is presented which explicitly takes into account the asymmetry of the gradient coil. It is shown both theoretically and experimentally that, in contrast to symmetric coils, an asymmetric coil generates concomitant field terms of zeroth and first order in space. Artifacts induced by concomitant fields can be much more pronounced for asymme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
121
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(134 citation statements)
references
References 8 publications
1
121
0
Order By: Relevance
“…the SNR or the calibration of high strength diffusion gradients system) that can systematically bias quantitative diffusion-MRI measurements [30], [32]. A limited number of studies have reported phantom data specific to the characterization of MR scanner systems for diffusion-MRI of the brain as well as the body [34][41], [43], [57], [58], [87], [88]. However, in diffusion-MRI of the breast, only a few clinical studies have incorporated a basic verification of the calibration of diffusion gradients [11], [22], [72], [89], [90].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…the SNR or the calibration of high strength diffusion gradients system) that can systematically bias quantitative diffusion-MRI measurements [30], [32]. A limited number of studies have reported phantom data specific to the characterization of MR scanner systems for diffusion-MRI of the brain as well as the body [34][41], [43], [57], [58], [87], [88]. However, in diffusion-MRI of the breast, only a few clinical studies have incorporated a basic verification of the calibration of diffusion gradients [11], [22], [72], [89], [90].…”
Section: Discussionmentioning
confidence: 99%
“…As a whole, these results indicate a mismatch between the theoretically assumed and the effective b-value . This could originate from errors in diffusion gradients amplitude, eddy current fields, concomitant field terms and cross terms between diffusion gradients and imaging gradients [2], [32], [87], [88], [95]. These factors are direction-dependent and can have deleterious effects that are more prominent at the high gradient strengths usually employed in diffusion-MRI [2], [32].…”
Section: Discussionmentioning
confidence: 99%
“…Additional ECG artifacts are induced inside the MRI bore by the MagnetoHydrodynamic (MHD) effect, which are not addressed in this paper. Interested parties can view previous publications 1, 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Nagy et al, 2007), and concomitant field terms (e.g. Meier et al, 2008). These deviations from the expected (linear) gradient performance and also other effects biasing the diffusion weighting, such as cross terms between diffusion-weighting gradients and imaging gradients (e.g.…”
Section: Introductionmentioning
confidence: 99%